Description of a new species of Orsillini (Hemiptera: Heteroptera: Lygaeidae: Orsillinae) from Argentina, with a key to the Argentinean Orsillini - Dellapé, Pablo M.; Montemayor, Sara I. (Zootaxa, 2012)
Aborsillus pora, the second species in the genus Aborsillus, is described and illustrated, the generic limits are discussed,new records to Argentinean Orsillini are provided, and a key to the Argentinean Orsillini as well as a distributional map for these species is given.